2016
DOI: 10.1155/2016/4505812
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Results: Safety and Efficacy of Secondary Piggyback SensarAR40 Intraocular Lens Implantation to Correct Pseudophakic Refractive Error

Abstract: In this study we evaluate the visual outcomes, safety, efficacy, and stability of implanting of second sulcus intraocular lens (IOL) to correct unsatisfied ametropic patients after phacoemulsification. Methods. Retrospective study of 15 eyes (15 patients) underwent secondary intraocular lens implanted into the ciliary sulcus. The IOL used was a Sensar IOL three-piece foldable hydrophobic acrylic IOL. The first IOL in all patients was acrylic intrabagal IOL implanted in uncomplicated phacoemulsification surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
5
2
1
Order By: Relevance
“…The spherical equivalent refraction was reduced from a mean of 1.02D–0.36D, with 57% and 76% of the eyes within 0.25D and 0.50D of the intended target, respectively. The percent of eyes within 0.50D is somewhat lower than that for other surgical solutions in other studies, 4 , 5 , 7 , 11 , 12 likely a function of the high percentage of eyes in the current study with a residual spherical equivalent refractive error of −0.625D. All of the previous studies 3 5 , 7 , 11 , 12 reported spherical equivalent refractions after at least 3 months postoperatively, which may also have been a factor.…”
Section: Discussioncontrasting
confidence: 56%
“…The spherical equivalent refraction was reduced from a mean of 1.02D–0.36D, with 57% and 76% of the eyes within 0.25D and 0.50D of the intended target, respectively. The percent of eyes within 0.50D is somewhat lower than that for other surgical solutions in other studies, 4 , 5 , 7 , 11 , 12 likely a function of the high percentage of eyes in the current study with a residual spherical equivalent refractive error of −0.625D. All of the previous studies 3 5 , 7 , 11 , 12 reported spherical equivalent refractions after at least 3 months postoperatively, which may also have been a factor.…”
Section: Discussioncontrasting
confidence: 56%
“…In terms of residual refraction, our study showed that 100% of eyes were within ±1 D: 88% of patients were within the emmetropia range −0.5 to 0.5 D, with 60% within ±0.25 D. Interestingly, the results are similar to those found with the AddOn IOL, in which 57% and 76% of eyes were within ±0.25 D and ±0.5 D, respectively 16. It is noteworthy to mention that refractive results after more recent studies of piggyback IOL implantation have improved, with results showing 93%–100% of patients within ±0.5 D of target refraction 13,17,18. Laser refractive surgery also provides very good refractive results and is considered more accurate than lens-based procedures 4,15.…”
Section: Discussionsupporting
confidence: 73%
“…This was performed to confirm the consistency of such measures to be used to optimize IOL power calculation in piggyback cases or in general practice to improve the characterization of ELP. It should be considered that the pseudophakic ACD is a crucial parameter in the calculation of the IOL power to implant in a piggyback mode, 21 and therefore the consistency of this type of pseudophakic anatomical measures must be tested and confirmed. Likewise, the relationship between pseudophakic ACD and ELP has been investigated, being both parameters significantly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…This level of intrasession or intraobserver repeatability is comparable to that reported for the same and other optical biometers when used for measuring phakic eyes. [10][11][12]14,[21][22][23] McAlinden at al 12 reported a S w value of 0.02 mm…”
mentioning
confidence: 99%